Sosialisasi Optimalisasi Pengembangan Kaum Milenial Melalui Ekonomi Islam Di SMK Triguna Dharma Besitang Kabupaten Langkat - Zaifatur Ridha; Hayatun Sabariah; Shelly Hannafi; Dhea Ananda Siregar; Winda Widia Wati; Citra Sovia; Fachri Iskandar; Nur Sari Asniah (Fusion: Jurnal Pengabdian kepada Masyarakat, 2023)
The millennial generation is a group that is very synonymous with digital technology. The millennial generation relies heavily on digital communication tools in their daily life. So that digital technology is no longer just a contemporary style but has become a necessity for various activities. This research was conducted to find out how far the potential of the millennial generation is in developing the Islamic economy. The research method uses a qualitative method which explains the behavior of Indonesia's millennial generation, especially at the Triguna Dharma Besitang Private Vocational School in digital technology and the potential that can be utilized for the development of the Islamic economy. The method of activity is by holding socialization seminars at the Triguna Dharma Besitang Private Vocational School. The results of activities in Community Service (PKM) activities can be concluded that the perceptions of Triguna Dharma Besitang Private Vocational School students about the Islamic economic system are very influential in everyday life. Because the Islamic economic system is in accordance with the provisions stipulated in Islam, which in practice prioritizes the welfare of the entire community. This can be realized if the application of Islamic economics starts from the millennial generation.